2022
DOI: 10.3389/fped.2021.752816
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Spectrum and Burden of Influenza-Associated Neurological Complications in Hospitalised Paediatric Patients

Abstract: BackgroundInfluenza is one of the most common causes of acute respiratory tract infections around the world. Influenza viruses can cause seasonal epidemics. There remains limited information on the impact of both seasonal influenza A and influenza B related hospitalisations from neurological complications in paediatric populations in Asia.ObjectivesTo examine both the clinical spectrum and healthcare burden of influenza-associated neurological complications (IANCs) within the paediatric population of Hong Kong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…23 Several recently published articles have described extra-pulmonary complications in hospitalized children with influenza B prior to the COVID-19 pandemic. [24][25][26][27] Geerdes-Fenge et al treated 17 hospitalized children with influenza B in northern Germany in the winter season of 2017-2018, and revealed that 5 (29.4%) suffered extrapulmonary complications, 24 lower than 42% (37/88) found in the present study (Table 1). A few studies focusing on neurologic involvement in hospitalized children with influenza B observed that approximately 10-15% of the patients had neurologic complications.…”
supporting
confidence: 41%
See 3 more Smart Citations
“…23 Several recently published articles have described extra-pulmonary complications in hospitalized children with influenza B prior to the COVID-19 pandemic. [24][25][26][27] Geerdes-Fenge et al treated 17 hospitalized children with influenza B in northern Germany in the winter season of 2017-2018, and revealed that 5 (29.4%) suffered extrapulmonary complications, 24 lower than 42% (37/88) found in the present study (Table 1). A few studies focusing on neurologic involvement in hospitalized children with influenza B observed that approximately 10-15% of the patients had neurologic complications.…”
supporting
confidence: 41%
“…Influenza can cause complications outside the respiratory system in both adults and children. [21][22][23][24][25][26][27] A large series study of 2330 hospitalized pediatric patients with influenza A (H1N1 pdm09) during the 2009-2010 pandemic in the USA revealed that 709 (30.4%) children had complications affecting the digestive, neurological, musculoskeletal and cardiovascular systems. 23 Several recently published articles have described extra-pulmonary complications in hospitalized children with influenza B prior to the COVID-19 pandemic.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Though generally considered as a mild disease, according to the latest estimate, 290,000-650,000 deaths due to influenza occur each year (2). Recent studies tend to focus on differences in symptoms between influenza strains (3,4). Still, several epidemiological characteristics between influenza A and B infections have been proven to be distinguishable (5).…”
Section: Introductionmentioning
confidence: 99%